Characteristics of in-situ hydrogen biomethanation at mesophilic and thermophilic temperatures. (October 2021) - Jiang, Hao; Wu, Fan; Wang, Yuchang; Feng, Lu; Zhou, Hongjun; Li, Yeqing
Highlights: Injected H2 was 100% consumed within short period. Hydrogen biomethanation performed superior at thermophilic temperature. Remaining CO2 of<10% cannot be removed by increasing H2 content and stirring intensity. Abstract: In-situ hydrogen biomethanation is a promising technology to upgrade biogas. The efficiency of biomethanation relies on various parameters, e.g. gas supplement, temperature and hydrogenotrophic methanogens. Therefore, it is important to investigate the characteristics of in-situ hydrogen biomethanation under different conditions. In this study, two experiments (lasted for 91 days and 105 days) were carried out to investigate the impacts of feeding gas and operating conditions on performances of reactors and microorganisms. During the whole experiment, no obvious fluctuation of pH and limitation of gas–liquid mass transfer were found. Results showed that the hydrogenotrophic methanogenesis performed better at thermophilic condition, while the dominant archaea genera at mesophilic and thermophilic temperature was determined to be Methanobacterium and Methanothermobacter, respectively. The highest CH4 content (greater than 90%) was obtained when H2 and CO2 was feeding at ratio of 4:1 and Methanothermobacter was dominant. These findings can provide useful information for promoting hydrogen biomethanation.